Varekai [videorecording (DVD)] - Morris, Nick; Champagne, Dominic (Columbia Tristar Home Video, 2003)
"Deep within a forest, at the summit of a volcano, there is an extraordinary world--a world where something else is possible. A world called Varekai. From the sky falls a solitary young man, and the story of Varekai begins. Parachuted into the shadows of a magical forest, a kaleidoscopic world populated by fantastical creatures, this young man sets off on an adventure both absurd and extraordinary."--Container.